Using ecosystem service bundles to detect trade-offs and synergies across urban–rural complexes - Yang, Guofu; Ge, Ying; Xue, Hui; Yang, Wu; Shi, Yan; Peng, Changhui; Du, Yuanyuan; Fan, Xing; Ren, Yuan; Chang, Jie (Landscape and Urban Planning, 2015)

Recoupling Industrial Dairy Feedlots and Industrial Farmlands Mitigates the Environmental Impacts of Milk Production in China - Fan, Xing; Chang, Jie; Ren, Yuan; Wu, Xu; Du, Yuanyuan; Xu, Ronghua; Liu, Dong; Chang, Scott X.; Meyerson, Laura A.; Peng, Changhui; Ge, Ying (Environmental Science & Technology, 2018)

A global strategy to mitigate the environmental impact of China’s ruminant consumption boom - Du, Yuanyuan; Ge, Ying; Ren, Yuan; Fan, Xing; Pan, Kaixuan; Lin, Linshan; Wu, Xu; Min, Yong; Meyerson, Laura A.; Heino, Mikko; Chang, Scott X.; Liu, Xiaozi; et al. (Nature Communications, 2018)
Abstract Rising demand for ruminant meat and dairy products in developing countries is expected to double anthropogenic greenhouse gas and ammonia emissions from livestock by 2050. Mitigation strategies are urgently needed to meet demand while minimizing environmental impacts. Here, we develop scenarios for mitigating emissions under local vs global supply policies using data from 308 livestock farms across mainland China, where emissions intensities are ~50% higher than those in developed nations. Intensification of domestic production and globalized expansion through increased trade result in reductions in global emissions by nearly 30% over a business-as-usual scenario, but at the expense of trading partners absorbing the associated negative externalities of environmental degradation. Only adoption of a mixed strategy combining global best-practice in sustainable intensification of domestic production, with increased green-source trading as a short-term coping strategy, can meet 2050 demand while minimizing the local and global environmental footprint of China’s ruminant consumption boom.